If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2 + x) = 72 (2 * 6 + x * 6) = 72 (12 + 6x) = 72 Solving 12 + 6x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = 72 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 72 + -12 6x = 72 + -12 Combine like terms: 72 + -12 = 60 6x = 60 Divide each side by '6'. x = 10 Simplifying x = 10
| -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 | | 6a+70=a | | 8x-151=49-2x | | 5x+3x-9=15 | | 3m^2-7m-40=0 | | -126+9x=39-2x | | -12-2x=-20 | | -93+4x=-6x+107 | | 4y=6y-12 |